2007
DOI: 10.1111/j.1475-2743.2007.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and nitrogen losses to surface waters from a forested feedlot for bulls in Finland

Abstract: Phosphorus and nitrogen losses to water from a forested feedlot (10 000 m 2 ) for 10 bulls was studied for 2 years in northwestern Finland. The nutrient loading was estimated by monitoring nutrient accumulation and migration in a feedlot soil profile and run-off to a nearby ditch. Ditch water was sampled for total phosphorus (TP), dissolved reactive P (DRP), total nitrogen (TN), NH 4 -N and NO 3 -N analyses. The concentrations of ammonium acetate extractable phosphorus (PAAA c ), NH 4 -N and NO 3 -N in the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…The ground was covered with twigs and grass. The vegetation and soil texture of the paddock area have been described in detail by Uusi-Kämppä et al (2007). A wooden fence separated the paddocks from each other.…”
Section: Animals and Housing Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ground was covered with twigs and grass. The vegetation and soil texture of the paddock area have been described in detail by Uusi-Kämppä et al (2007). A wooden fence separated the paddocks from each other.…”
Section: Animals and Housing Environmentsmentioning
confidence: 99%
“…Manninen et al 2008), and one way of reducing these costs is to overwinter growing cattle outdoors. For example, in Taivalkoski, North-Eastern Finland (65º34'N, 28º14'E), 400-600 growing animals are every year raised on very extensive forested land (0.5 animal unit ha -1 ) (Uusi-Kämppä et al 2007). Huuskonen et al (2009) and Tuomisto et al (2009) reported that finishing bulls can be overwintered outdoors with reasonable live weight gains in Northern Finland without warm housing facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Manninen et al 2008), and one method of reducing these costs is to overwinter growing cattle outdoors. For example, in Taivalkoski, North-Eastern Finland (65º34'N, 28º14'E), 400-600 growing animals are every year raised on very extensive forested land (0.5 animal unit ha -1 ) (Uusi- Kämppä et al 2007). Hands-on experience in Taivalkoski (Lehtiniemi et al 2001) indicates that young cattle perform quite well outdoors during wintertime, if the facilities are equipped with a rain shelter to cover a dry resting area with sufficient bedding material available to keep the animals dry and clean.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a P indexing system was developed to identify the vulnerability to P loss of areas or fields [8]. Similar to cropped soils, high concentrations of easily soluble P in soil surface from intensive beef production systems are associated with high concentrations of solu0 ble reactive P and total P in percolated water [9]. Kleinman et al [10] found that the concentration of dissolved reactive P in water runoff was positively correlated with water soluble P concentration in surface-applied manure.…”
Section: Introductionmentioning
confidence: 99%